(untitled) (Research, Society and Development, 2021)
To get to know the family influence over women’s choice for planned home birth. It is an exploratory descriptive research, a qualitative approach. Data was collected through semi structured interviews, recorded, transcribed and submitted to content analysis. The sample, obtained through data saturation, was composed by six women that delivered at least one child in a planned home birth, in cities in the state of Rio de Janeiro. Emerged two subject fields: family convincing attempt and partner support as a decisive factor in woman’s choice for planned home birth. Empowering, safety and self-esteem are important outcomes when there is support from the partner, much more than other family members.